If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) = 2(5 + 3x) Reorder the terms: 3(-5 + 2x) = 2(5 + 3x) (-5 * 3 + 2x * 3) = 2(5 + 3x) (-15 + 6x) = 2(5 + 3x) -15 + 6x = (5 * 2 + 3x * 2) -15 + 6x = (10 + 6x) Add '-6x' to each side of the equation. -15 + 6x + -6x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 -15 + 0 = 10 + 6x + -6x -15 = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 -15 = 10 + 0 -15 = 10 Solving -15 = 10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x-y=200 | | 4(x+7)+3(3x-7)=72 | | (3x+4)(4x+1)-(2x+3)(x+3)=(5x+2)(2x+1) | | 14x-18=12-6x | | -4x-150=66-12x | | 0.19y+0.06(y+6000)=1860 | | 8x+16y=640 | | 3/4*b=8 | | 5s=4 | | -7y+3= | | 6x-y=-23 | | -2u=-2/9 | | -6(-3y+6)-4y=5(y-8)-2 | | 7-2b=2b+6 | | Y=17-4y-2 | | x/4=5/12-6-x/15 | | -3v+6v=-20-1 | | 1/4(20d-16)=5d-4 | | -9+11=6x-8x | | X=21/5/8 | | 1/3(6-3a)=6 | | (2/(16x^2-4))-(2/(8x^2-8x-6)) | | 45-15=5(x-6) | | (3n+1)(n+3)+5=40 | | 7^-3/x^-2 | | 7q-13=3q+3 | | -4+3(-6n-1)=-2(-4n+5)-2 | | 5x+7.5= | | 30x-12=12x-6 | | 4y=-3.8 | | .35+3x=.45+2x | | -2y+6+3y=6 |